Pengaruh Murrotal Al Quran Terhadap Intensitas Nyeri Persalinan : Systematic Literature Review - Nova Avianti Rahayu; Sarah Fitria (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2022)
Childbirth is a physiological process that allows a series of major changes in the mother to be able to give birth to her fetus through the birth canal. Labor pain is a reaction to uterine muscle contractions that normally occur during labor. However, many mothers cannot bear the pain because it is influenced by stress. The purpose of this study was to find evidence based on the effectiveness of the murrotal al-Quran on the intensity of labor pain. This review uses the systematic literature review method which consists of eight stages, namely identifying midwifery problems, priority problems and research questions, primary and secondary data frameworks, identification of relevant studies, prism flow diagrams, critical appraisal, data analysis and data extraction. This review uses 2 databases with a period from 2010-2020. The total articles obtained were 356 articles, 12 articles were selected for review. Several articles comparing labor pain in the intervention group with murrotal al-quran and no intervention, obtained the results that murrotal al-quran is an effective non-pharmacological pain management for reducing labor pain in stage I. The conclusion from this review is that murrotal al-quran is effective for reducing pain intensity during labor in stage I.